Risk stratification of ibrutinib toxicity co-administered with triazole antifungals: insights from real-world pharmacovigilance and clinical evidence - Shiyun Li; Zijuan Li; Shiqiao Wang (Frontiers in Medicine, 2026)
Objective The co-administration of ibrutinib and triazole antifungals results in known pharmacokinetic interactions, but the comprehensive clinical risk profile and grading characteristics remain underexplored. This study integrated real-world pharmacovigilance data, clinical pharmacokinetic studies, and published clinical cases to evaluate the comparative safety profiles and risk gradients of these drug combinations. Methods Adverse drug events (ADEs) from the FDA Adverse Event Reporting System (FAERS) between Q1 2013 and Q2 2025 were analyzed. Disproportionality analyses utilizing the reporting odds ratio (ROR) and proportional reporting ratio (PRR) were employed to detect event reporting signals across ibrutinib without triazole, triazole without ibrutinib, and combination therapy groups. The time-to-onset (TTO) was assessed via Weibull distribution analysis. A systematic review of 18 individual patient cases reported in 11 publications and relevant pharmacokinetic data supported clinical interpretation. Results Among the submitted reports, serious outcomes accounted for 66.95% of those involving combination therapy, compared with 46.38% for ibrutinib without triazole and 46.85% for triazole without ibrutinib, respectively. Strong cytochrome P450 3A (CYP3A) inhibitors increased ibrutinib exposure by 5.7– to 10.3-fold, whereas isavuconazole increased exposure by approximately 2.1-fold. Voriconazole-containing reports showed a signal for cerebral aspergillosis (ROR = 474.61, n = 3), posaconazole-containing reports showed cardiac events including pericardial effusion (ROR = 24.95, n = 4), and isavuconazole-containing reports showed a signal for febrile neutropenia (ROR = 29.7, n = 4). For combination therapy reports with analyzable date information (157/590, 26.6%), the median reported onset was 63 days. Conclusions The identified pharmacovigilance signals are clinically interpretable in light of known CYP3A-mediated pharmacokinetic interactions, but they should be considered hypothesis-generating rather than causal. These findings support clinical awareness, individualized medication review, and further validation in studies with defined denominators and appropriate control of confounding.